2016
DOI: 10.2217/fon-2016-0344
|View full text |Cite
|
Sign up to set email alerts
|

3D Ct Scan for Perioperative Identification of Anatomical Variations of Lungs

Abstract: 3D CT scan should be performed before surgery if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Contrast‐enhanced CTA with 3D reconstruction imaging has been proven to better assess feeding vessels, local tumor expansion, and loco‐regional invasion. It facilitates a more detailed preoperative assessment of surgical feasibility and safety . This innovative imaging technique has the potential to improve stratification of patients for more tailored therapy and better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast‐enhanced CTA with 3D reconstruction imaging has been proven to better assess feeding vessels, local tumor expansion, and loco‐regional invasion. It facilitates a more detailed preoperative assessment of surgical feasibility and safety . This innovative imaging technique has the potential to improve stratification of patients for more tailored therapy and better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates a more detailed preoperative assessment of surgical feasibility and safety. 6,27,28 This innovative imaging technique has the potential to improve stratification of patients for more tailored therapy and better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed that by using preoperative 3D reconstruction it was possible to accurately identify up to 98% of surgically relevant and potentially complicating pulmonary artery branches, including anomalous or uncommon variations in vascular branching patterns. Thereby, 3D reconstruction facilitates surgical resections by avoiding blind dissection of vessels and increases surgeons confidence in their knowledge of the spatial relationship between the lesion and adjacent anatomical structures in the individual patient (18,19,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Identification Of Anatomical Landmarks and Interindividual V...mentioning
confidence: 99%
“…Two thoracic groups have demonstrated that the aid of 3D reconstructions, of the lung and heart, are very useful to obtain preoperative information before VATS surgery [16,17]. The 3D reconstruction could also forecast a reliable body reconstruction for futuristic self-determining robotic surgery.…”
Section: Future Researchmentioning
confidence: 99%